Clinical Characteristics and Management of Pediatric Eye Trauma in National Tertiary Eye Hospital in Indonesia - Axa, Alya Putri; Amiruddin, Primawita Oktarima; Caesarya, Sesy (Jurnal Profesi Medika : Jurnal Kedokteran dan Kesehatan, 2024)
Eye trauma is a major cause of vision problems in children, leading to visual impairment and blindness. This issue has significant global implications, affecting children psychologically and socially. According to the American Academy of Pediatrics, 66% of all eye traumas occur in individuals under 16, with the highest occurrence between ages 9 and 11. We conducted a retrospective descriptive study using medical records of pediatric patients aged 0 - 18 years who experienced eye trauma from January to December 2022 at the National Eye Center-Cicendo Eye Hospital. There were 190 patients included in this study. The majority of patients were male (69.47%) and the most common age group affected was 6 - 12 years (33.16%). Leading causes of eye trauma were blunt trauma (58.95%). The common management for eye trauma in this study is operative or medical procedures (67,37%) This study provides valuable information on the characteristics and management of eye trauma in children, which can contribute to the development of prevention strategies and appropriate interventions. Understanding the patterns of eye trauma and implementing comprehensive care can help prevent blindness and minimize visual impairment. Keywords: Eye Trauma; Children; Management